PENINGKATAN MUTU PERGURUAN TINGGI MELALUI RENCANA STRATEGIS - Intan Putri Azhari; Bustamin (Politeknik STIA LAN Makassar, 2020)
Achieving accreditation for higher education in Indonesia remains the main goal to be achieved in both public and private locations. Due to the complexity of complying with the indicator standards set by BAN-PT, the accreditation process often becomes a nuisance for universities. This is especially true for universities that do not yet have a good strategic plan. To meet these dates, they are often manipulated to get the maximum accreditation rating, but unfortunately, objectivity is sacrificed. The purpose of this paper is to analyze the improvement in the quality of universities in Indonesia. This article uses a research library that uses a qualitative descriptive approach that collects secondary data in the form of journals and related documents and then analyzes it using Creswell analysis. The results showed that the government has made efforts to improve the quality of universities in Indonesia through the quality assurance system, including SPMI, SPME, and PD Dikti. SPME innovations continue to be carried out, ranging from seven standards to nine criteria. To support the implementation of SPMI and SPME, each university needs to show strong commitment and be supported by the availability of good strategic planning, as literature research shows the importance of strategic planning to improve the quality of higher education.